Women’s Agency in Feudal Sindh: Ambivalent Negotiations of Honor, Patriarchy, and Everyday Resistance - Benazeer Chandio (Journal of Religion and Society, 2025)
This paper will provide a critical analysis of how women in feudal zones in Sindh, Pakistan, utilize their agency in societies where systems of honor, patriarchy, and socio-economic control prevail. Through semi-structured interviews with fifteen women in rural Sindh, this qualitative study will use interpretivist to analyze how women negotiate their agency in contexts of constriction. The study is based on an interpretive, rather than representative, sample, providing unique and context-specific insight into how agency is performed when constrained by structural circumstances. The theoretical frameworks used for the interpretation include feminist theories, postcolonial feminism, everyday resistance, and patriarchal bargaining. It is shown that women perform their agency through the use of strategic conformity, indirect decisions, emotional work, and reinterpretation of honor. However, another dimension becomes apparent, whereby some of the agency strategies that women employ help maintain patriarchal structures. In the process of developing an understanding of the latter, the concept of ambivalent agency will be introduced. Moreover, highly publicized cases are studied as discourses creating fear within, risk perceptions, and normative boundaries of appropriate feminine behavior. Thus, by addressing these processes, the research does not fall into the trap of the simplistic dichotomy of either being a victim or a resistor. The research will make a theoretical contribution to the literature on feminism through the provision of an insightful contextual understanding of the notion of agency within feudal societies. Keywords: Women’s Agency, Feudalism, Honor Culture, Sindh, Ambivalent Agency, Everyday Resistance, Patriarchal Bargaining